Municipal Finances: A Handbook for Local Governments - Farvacque-Vitkovic, CatherineD. (World Bank, 2015)
The Municipal Finance Handbook aims to help local government practitioners, particularly staff of medium and large cities, improve strategic management of municipal finances. The demands for pragmatic knowledge are fueled in part by decentralization and fiscal pressures, as transfer of responsibilities from central to local governments are not often accompanied with an adequate transfer of resources. Practitioners seek ideas and tools to control expenditures, strengthen revenues, as well as to tap large external funds, achieve creditworthiness, and adopt good borrowing practices.